Financial reporting quality and disclosure on stock price of listed deposit money banks in Nigeria - Adebanjo, Adeleke Abdulyekini; Wisdom, Okere (Asian Journal of Empirical Research, 2024)
Due to the lack of a regulatory framework, financial scandals, fraud and poor disclosure in financial reports, investors and other stakeholders lose confidence in the firm's performance, which could lead to lower share prices. Investors and financial analysts who have noticed the impact of accounting quality and disclosures on stock prices have necessitated this study. This study looked at the impact of financial reporting quality and disclosure on the stock price of listed deposit money banks in Nigeria. The study made use of secondary data gathered from the annual report of listed DMB in Nigeria. The data generated were analysed using descriptive statistics, correlation analysis and Panel ordinary least square regression to understand the degree of relationship among the variables. A correlation matrix was carried out to test for multi-collinearity within the selected variables. Findings revealed that the combined effect of financial reporting quality and disclosure has a positive and significant impact on the stock price of listed deposit money banks in Nigeria. The study thereby recommends that for financial institutions to achieve sustainable performance levels, they should ensure that they meet stakeholders’ demands, which mainly rest on accounting information comprehensiveness and quality. Furthermore, the quality of accounting should be improved by ensuring companies adhere to accounting standards and financial regulations regarding disclosures.